(untitled) (PANGEEA, 2025)
ABSTRACT: Forest models are becoming essential tools in forest research, management, and policymaking but are currently under deep transformation. In this review of the most recent literature (2018–2023), I analysed an updated general view of the main topics currently attracting the efforts of forest modellers, the trends already in place, and some of the current and future challenges the field will face. Four major topics attracting the most of current modelling efforts: data acquisition, productivity estimation, ecological pattern predictions, and forest management related to ecosystem services. Although the topics may seem different, they all converge towards integrated modelling approaches by the pressure of climate change as the major coalescent force, pushing current research efforts into integrated mechanistic, cross-scale simulations of forest functioning and structure. I analysed that forest modelling is experiencing an exciting but challenging time, due to the combination of new methods to easily acquire massive amounts of data, new techniques to statistically process such data, and refinements in mechanistic modelling that incorporate higher levels of ecological complexity and breaking traditional barriers in spatial and temporal scales. However, new available data and techniques are also creating new challenges. In any case, forest modelling is increasingly acknowledged as a community and interdisciplinary effort. As such, ways to deliver simplified versions or easy entry points to models should be encouraged to integrate non-modeller stakeholders into the modelling process since its inception. This should be considered particularly as academic forest modellers may increase urban forest models’ ecological and mathematical complexity. The Geographical axis system includes cities in Mures and Bistriţa-Năsăud counties. Cities in Bistriţa-Năsăud: Bistriţa-Beclean-Năsăud-Sângeorz-Băi. in Mures: Târgul Mureş-Reghin-Luduş, Keywords: Forest modelling; strategy; Urban forestry Methods; Geographical axis; NDVI;